2013
DOI: 10.1111/anu.12038
|View full text |Cite
|
Sign up to set email alerts
|

Growth, feed utilization, body composition and swimming performance of giant croaker,Nibea japonicaTemminck and Schlegel, fed at different dietary protein and lipid levels

Abstract: A 50‐day feeding trial was conducted to examine the effects of dietary protein and lipid levels on growth, feed utilization, body composition and swimming performance of giant croaker, Nibea japonica. Fish (initial body weight 44.6 g ind−1) were fed ten test diets which were formulated at 5 crude protein levels (360, 400, 440, 480 and 520 g kg−1) and 2 crude lipid levels (90 and 150 g kg−1). In addition, a raw fish diet (fillet of small yellow croaker) served as the reference. The weight gain (WG) increased, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 29 publications
9
37
0
1
Order By: Relevance
“…As expected, dietary energy increased from 17.50 to 23.10 kJ/g with increasing dietary lipid, but because the diets used in the present study were isoproteic, the dietary protein (P) to energy (E) ratio decreased, from 23.25 to 17.56 gP/MJ, as dietary lipid increased (Table 1). The experimental lipid level that elicited the best results for the Gulf corvina (11%) corresponds to a P/E ratio of 20.42 gP/MJ, which concurs with the range of P/E ratios, from 20.7 to 28.6 gP/MJ, known to produce optimal growth of other sciaenids, such as A. japonicus, A. regius, S. ocellatus, N. japonica, N. miichthioides, and Totoaba macdonaldi (Chai et al, 2013;Chatzifotis et al, 2012;Martínez-Llorens et al, 2011;McGoogan and Gatlin, 1999;Pirozzi et al, 2010;Rueda-López et al, 2011;Turano et al, 2002;Wang et al, 2006;Woolley et al, 2010) (values were either directly taken or calculated from dietary protein and energy content data reported by the authors). Comparable optimal P/E ratios also have been reported for other seawater carnivorous, non-sciaenid fish, such as Dentex dentex (19.5 gP/MJ for 10-g fingerlings, and 23.7 gP/MJ for 92.4-g juveniles), Lateolabrax japonicus (25.9 gP/MJ), Pleuronectes americanus (26.6 gP/MJ), and Rachycentrum canadum (22.4-28.8 gP/MJ) (Ai et al, 2004;Hebb et al, 2003;Skalli et al, 2004;Wang et al, 2005).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As expected, dietary energy increased from 17.50 to 23.10 kJ/g with increasing dietary lipid, but because the diets used in the present study were isoproteic, the dietary protein (P) to energy (E) ratio decreased, from 23.25 to 17.56 gP/MJ, as dietary lipid increased (Table 1). The experimental lipid level that elicited the best results for the Gulf corvina (11%) corresponds to a P/E ratio of 20.42 gP/MJ, which concurs with the range of P/E ratios, from 20.7 to 28.6 gP/MJ, known to produce optimal growth of other sciaenids, such as A. japonicus, A. regius, S. ocellatus, N. japonica, N. miichthioides, and Totoaba macdonaldi (Chai et al, 2013;Chatzifotis et al, 2012;Martínez-Llorens et al, 2011;McGoogan and Gatlin, 1999;Pirozzi et al, 2010;Rueda-López et al, 2011;Turano et al, 2002;Wang et al, 2006;Woolley et al, 2010) (values were either directly taken or calculated from dietary protein and energy content data reported by the authors). Comparable optimal P/E ratios also have been reported for other seawater carnivorous, non-sciaenid fish, such as Dentex dentex (19.5 gP/MJ for 10-g fingerlings, and 23.7 gP/MJ for 92.4-g juveniles), Lateolabrax japonicus (25.9 gP/MJ), Pleuronectes americanus (26.6 gP/MJ), and Rachycentrum canadum (22.4-28.8 gP/MJ) (Ai et al, 2004;Hebb et al, 2003;Skalli et al, 2004;Wang et al, 2005).…”
Section: Discussionsupporting
confidence: 79%
“…For the yellow croaker, Pseudosciaena crocea, Duan et al (2001) reported optimal dietary crude fat and protein levels to be 10.5 and 47%, respectively. In turn, Chai et al (2013) suggested dietary crude fat and protein levels of 9.0 and 48%, respectively, as optimal for the giant croaker, N. japonica. Finally, a diet combining 18% crude fat and 46% crude protein produced the best growth performance of juvenile A. japonicus (Woolley et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…; Chai et al . ), our results confirm that there is an optimum protein/energy ratio for tilapia diets in this phase.…”
Section: Discussionsupporting
confidence: 86%
“…Energy levels of experimental diets (14.6-16.5 kJ/g) were achieved as previously described for giant croaker Nibea japonica (Lee et al 2001;Chai et al 2013). The gross energy value of each diet was determined by using values of 16.7 kJ/g protein, 16.7 kJ/g carbohydrate and 37.6 kJ/g lipid (Garling and Wilson 1976).…”
Section: Experimental Dietsmentioning
confidence: 99%
“…It classified in suborder Percoidei, family Sciaenidae and genus Nibea, and is distributed widely in India, the Philippines, and the South and East China Sea (Cheng Cheng 1987;Shen et al 2004). Chu's croaker is good candidate for aquaculture because it possesses some desirable characteristics including tolerance to widely varying salinity and temperatures (Chai et al 2013). In addition to its excellent local market of southeastern Asia attained as a result of the high tonic function of its swimming bladder, chu's croaker is also appreciated for its tasty flesh by foreign consumers.…”
Section: Introductionmentioning
confidence: 99%